2014
DOI: 10.1002/2013wr014700
|View full text |Cite
|
Sign up to set email alerts
|

Many‐objective reservoir policy identification and refinement to reduce policy inertia and myopia in water management

Abstract: This study contributes a decision analytic framework to overcome policy inertia and myopia in complex river basin management contexts. The framework combines reservoir policy identification, manyobjective optimization under uncertainty, and visual analytics to characterize current operations and discover key trade-offs between alternative policies for balancing competing demands and system uncertainties. The approach is demonstrated on the Conowingo Dam, located within the Lower Susquehanna River, USA. The Low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 143 publications
(96 citation statements)
references
References 90 publications
0
94
0
Order By: Relevance
“…Examples of the application of RO in the development of long-term water management strategies can be found in Kwakkel et al (2014), Giuliani et al (2014), Herman et al (2014), Kang and Lansey (2013) and Beh et al (2015b) and for adaptive policymaking in Hamarat et al (2012). Within this research it was found that RO could handle complex, deeply uncertain problems with large numbers of possible solutions.…”
Section: The Current Approach Within the Uk As Stated In The Environmentioning
confidence: 88%
“…Examples of the application of RO in the development of long-term water management strategies can be found in Kwakkel et al (2014), Giuliani et al (2014), Herman et al (2014), Kang and Lansey (2013) and Beh et al (2015b) and for adaptive policymaking in Hamarat et al (2012). Within this research it was found that RO could handle complex, deeply uncertain problems with large numbers of possible solutions.…”
Section: The Current Approach Within the Uk As Stated In The Environmentioning
confidence: 88%
“…The decision analytic framework proposed by Giuliani et al (2014) combines reservoir policy identification and many-objective optimization under uncertainty to characterize the current baseline operations of the Conowingo reservoir and discover key tradeo↵s between alternative operating policies. In Giuliani et al (2014), two formulations of the MODPS problem are contrasted: the historical case, as formulated in eq.…”
Section: Application Resultsmentioning
confidence: 99%
“…They are defined as multiinput multi-output RBFs (accounting for 32 parameters), which provide the release decision vector u t (i.e., the downstream release as well as the ones for the public water supply) as a function of time t and reservoir level h t . Six operating objectives measures the multi-stakeholder interests a↵ected by the Conowingo reservoir operation (for further details about the problem formulation see Giuliani et al, 2014): -Hydropower revenue (to be maximized); -Atomic Power Plant, Baltimore, and Chester water supply volumetric reliability (to be maximized); -Recreation, modeled by the storage reliability (to be maximized); -Environment, modeled by the shortage index with respect to FERC flow requirements (to be minimized).…”
Section: Case Study Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the decision variables used in optimisation-based WRM approaches, these are almost exclusively modelled as deterministic. However, this often results in rigid, precautionary strategies that may not be sufficiently flexible to adapt to uncertain future changes (Basupi and Kapelan;Giuliani et al, 2014b;Mortazavi et al, 2013a;Woodward et al, 2014).…”
Section: Current Statusmentioning
confidence: 99%